Business Improvement Strategy Using Digital Marketing In The Informal Sector Of A Stove Factory In Joyo Agung Malang - Anam, Rifqi Khairul (Pusmedia Group Indonesia, 2024)
Community service is an essential obligation of higher education that lecturers must do in order to impart information and broaden the public's understanding in numerous domains. The activities scheduled take place in the stove plant located at Jl. Joyo Agung No. 60, Tlogomas, Kec. Lowokwaru, Malang City. An example of a community service activity is using marketing methods that utilize information technology to assist the informal sector. The researchers employed the Participatory Action Research (PAR) approach to actively engage with stove factory players in the field and educate them on the utilization of social media for online marketing of stoves.